Attributes Underlying Non-surgical Treatment Choice for People With Low Back Pain: A Systematic Mixed Studies Review - Poder, Thomas G.; Beffarat, Marion (International journal of health policy and management, 2021)
Background: The knowledge of patients’ preferences in the medical decision-making process is gaining in importance. In this article we aimed to provide an overview on the importance of attributes underlying the choice of non-surgical treatments in people with low back pain (LBP). Methods: A systematic mixed studies review was conducted. Articles were retrieved from the search engines PubMed, ScienceDirect, and Scopus through June 21, 2018. The Mixed Methods Appraisal Tool (MMAT) was used to assess the quality of the study, and each step was performed by 2 reviewers. Analysis: From a total of 390 articles, 13 were included in the systematic review, all of which were considered to be of good quality. Up to 40 attributes were found in studies using various methods. Effectiveness, ie, pain reduction, was the most important attribute considered by patients in their choice of treatment. This attribute was cited by 7 studies and was systematically ranked first or second in each. Other important attributes included the capacity to realize daily life activities, fit to patient’s life, and the credibility of the treatment, among others. Discussion: Pain reduction was the most important attribute underlying patients’ choice for treatment. However, this was not the only trait, and future research is needed to determine the relative importance of the attributes.